2009
DOI: 10.1007/s00418-009-0568-2
|View full text |Cite
|
Sign up to set email alerts
|

MAPK mediates Hsp25 signaling in incisor development

Abstract: Rodent incisors are continuously growing teeth that include all stages of amelogenesis. Understanding amelogenesis requires investigations of the genes and their gene products control the ameloblast phenotype. One of the mechanisms related to tooth differentiation is mitogen-activated protein kinase (MAPK) signaling. The extracellular-signal regulated kinase (ERK)/mitogen-activated protein kinase kinase (MEK) cascade is associated with mechanisms that control the cell cycle and cell survival. However, the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Moreover, the identification of molecular mechanisms by which the scaffolds direct odonto-progenitors into odontogenic differentiation is of great interest to scientists in this field. 14,15 In this study, we compared the efficacy of five kinds of scaffolds for DPSC proliferation and odontogenic differentiation in vitro and the regeneration of dentin-like hard tissue in vivo. We further investigated how these scaffolds regulate odontogenic differentiation of DPSC through signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the identification of molecular mechanisms by which the scaffolds direct odonto-progenitors into odontogenic differentiation is of great interest to scientists in this field. 14,15 In this study, we compared the efficacy of five kinds of scaffolds for DPSC proliferation and odontogenic differentiation in vitro and the regeneration of dentin-like hard tissue in vivo. We further investigated how these scaffolds regulate odontogenic differentiation of DPSC through signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recent studies have found that MAPK signaling is involved during dental pulp cell differentiation and tooth development. [13][14][15] However, whether the MAPK signaling pathways play an important role in the dentinogenic capacity of DPSCs and whether scaffolds could affect the MAPK signaling pathways of DPSCs have not been assessed.…”
Section: Introductionmentioning
confidence: 98%
“…For the immunohistochemical staining, a modification of a previously described method (Lee et al. 2009) was used.…”
Section: Methodsmentioning
confidence: 99%
“…For the immunohistochemical staining, a modification of a previously described method (Lee et al 2009) was used. In brief, the tissue section was blocked in 3% hydrogen peroxide for 15 min, pre-treated by boiling in 10 mmol L )1 citrate buffer (pH 6.0) for 5 min and cooled at room temperature.…”
Section: Immunohistochemical Analysis Using Nestinmentioning
confidence: 99%
“…In their recent work, Lee et al (2009) explored mitogen-activated protein kinase (MAPK) signaling during incisor development and growth in the mouse. By using pharmaceutical activation and inhibition of MAPKs in in vitro cultures, important functions of MAPKs for amelogenesis were found, which were partly involving Hsp25 signaling activated by phosphorylated ERK and MEK.…”
Section: Smooth Musclementioning
confidence: 99%